Šolska knjižnica in nadarjeni učenci v tretjem vzgojno-izobraževalnem obdobju na Osnovni šoli Prule - Škrlj, Gregor (Šolska knjižnica, 2014)
The school library offers help in the work with talented students during various school subjects and during all age periods.The paper presents the aspect of the school library and school librarian in the work with talented students in the third triad, specifically in the teaching of additional higher-level English classes. The idea for specific co-operation in the work with the talented stems from the planning of crosscurricular lessons of Library and Information Knowledge and English in the third triad. We present the library, the materials for the work with the talented, their characteristics, and a short insight into the work itself.
Keywords: angleščina; dodatni pouk; IKT; nadarjeni učenci; nadarjenost; osnovne šole; šolske knjižnice